Global Uncertainty - Giovanni Caggiano; Efrem Castelnuovo (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We estimate a novel measure of global financial uncertainty (GFU) with a dynamic factor framework that jointly models global, regional, and country-specific factors. We quantify the impact of GFU shocks on global output with a VAR analysis that achieves set-identification via a combination of narrative, sign, ratio, and correlation restrictions. We find that the world output loss that materialized during the great recession would have been 13% lower in absence of GFU shocks. We also unveil the existence of a global finance uncertainty multiplier: the more global financial conditions deteriorate after GFU shocks, the larger the world output contraction is.
Keywords: C32; E32; 330; Global Financial Uncertainty; dynamic hierarchical factor model; structural VAR; world output loss; global finance uncertainty multiplier